India's Strategic Considerations With Russia In The Post-Russia-Ukraine War Era - Tran, Loc Hai My (Department of Political Science - Universitas Sains Al-Qur’an, 2024)
This article examines India's strategic considerations in the aftermath of the Russia crisis, explicitly focusing on India-Russia relations. The article analyses the factors influencing India's approach towards Russia, particularly in defense cooperation while considering the implications of China's rising influence on India's strategic calculations. By conducting a case study of India-Russia relations, the paper investigates the dynamics of defense collaboration, the significance of Russia as a defense partner for India, and the evolving regional security landscape shaped by China's ascent. The research provides insights into India's strategic alignments and decision-making processes in the post-Russia crisis era, considering Russia's new foreign policy emphasizing India and China. Furthermore, the paper examines the encircling impact of China's rising influence in South Asia on India, highlighting India's abstention in the UN General Assembly resolution condemning Russia's invasion of Ukraine as a reflection of its difficult position amidst these geopolitical developments. The findings of this research contribute to the understanding of India's strategic responses and decision-making frameworks in the context of shifting regional dynamics, considering the implications of Russia's foreign policy approach and China's growing power.